Biomimetic Approaches to the Synthesis of Natural Disesquiterpenoids: An Update - Diego Caprioglio; Stefano Salamone; Federica Pollastro; Alberto Minassi (Plants, 2021)
Natural disesquiterpenoids represent a small group of secondary metabolites characterized by complex molecular scaffolds and interesting pharmacological profiles. In the last decade, more than 400 new disesquiterpenoids have been discovered and fully characterized, pointing out once more the “magic touch” of nature in the design of new compounds. The perfect blend of complex and unique architectures and biological activity has made sesquiterpene dimers an attractive and challenging synthetic target, inspiring organic chemists to find new and biomimetic approaches to replicate the efficiency and the selectivity of natural processes under laboratory conditions. In this work, we present a review covering the literature from 2010 to 2020 reporting all the efforts made in the total synthesis of complex natural disesquiterpenoids.